Organoid biobanking, autonomy and the limits of consent - Lewis, Jonathan (Bioethics, 2022)
In the debates regarding the ethics of human organoid biobanking, the locus of donor autonomy has been identified in processes of consent. The problem is that, by focusing on consent, biobanking processes preclude adequate engagement with donor autonomy because they are unable to adequately recognize or respond to factors that determine authentic choice. This is particularly problematic in biobanking contexts associated with organoid research or the clinical application of organoids because, given the probability of unforeseen and varying purposes for which a donor's organoids could be employed and given the different ways in which a donor can relate to her biospecimens, a donor can value her organoids differently in different contexts, and her reasons for autonomously permitting use of her cells and tissues in one case may not support an autonomous decision in another. In response, this paper has three aims: first, to make the case for why organoid biobanks ought to respect donor autonomy conceived as authentic choice; second, to explore the autonomy-respecting limits of established and widely prevalent models of biobank consent; and third, to propose certain conditions that organoid biobanks ought to support or facilitate in order to respect donor autonomy.